Bayesian Classification of Affordances from RGB Images - Mur, Lorenzo; Martínez-Cantín, Rubén (Jornada de Jóvenes Investigadores del I3A, 2022)
We propose a Bayesian classification model using Deep Ensembles (DE) and MC-Dropout (MC-D) to predict affordances from RGB images. Our Bayesian model obtains a higher performance than previous works and captures the aleatoric and epistemic uncertainty, showing consistency with the type of objects and scenarios.